2015
DOI: 10.1080/01635581.2015.1087040
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Enriched Tomato Extract Inhibits Hypoxia, Angiogenesis, and Metastatic Markers in early Stage N-Nitrosodiethylamine Induced Hepatocellular Carcinoma

Abstract: Targeting altered pathways during initial stage of hepatocellular carcinoma (HCC) development is viewed as an effective and promising strategy to control this disease. Present study investigated the potential effect of lycopene-enriched tomato extract (LycT) on hypoxia-induced factor (HIF)-1α, HOX, VEGF, CD31, matrix metalloproteinase (MMP)-2, MMP-9, and alpha fetoprotein (AFP)expression during initial stages of N-nitrosodiethylamine (NDEA) induced HCC. Female Balb/c mice (8-10 wk) were assigned to 4 groups: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Interestingly, inhibition of angiopoietin–TEK pathway by all‐ trans retinoic acid has been described in EC1 human cellular line of esophagus cancer, which is in agreement with our results, taking into account that β‐cryptoxanthin is a provitamin A carotenoid. Such antiangiogenic capacity against development of several diseases has been previously proposed for several carotenoids, including β‐cryptoxanthin, based on chemoprotection studies . Yet, to the best of our knowledge, the present work represents the first report on β‐cryptoxanthin antiangiogenic effect on endothelial‐cells.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Interestingly, inhibition of angiopoietin–TEK pathway by all‐ trans retinoic acid has been described in EC1 human cellular line of esophagus cancer, which is in agreement with our results, taking into account that β‐cryptoxanthin is a provitamin A carotenoid. Such antiangiogenic capacity against development of several diseases has been previously proposed for several carotenoids, including β‐cryptoxanthin, based on chemoprotection studies . Yet, to the best of our knowledge, the present work represents the first report on β‐cryptoxanthin antiangiogenic effect on endothelial‐cells.…”
Section: Discussionsupporting
confidence: 50%
“…Interestingly most carotenoids have the ability to influence angiogenesis, mainly inhibiting it. This effect could explain some of their healthy actions . Indeed, carotenoid intake prevents macular‐degeneration risk associated to aging .…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were also noticed by Farooq et al [41] and Gangar et al [42] , who also observed the alterations in various hematological parameters in patients suffering from gastric and forestomach carcinoma respectively. LycT treatment to NDEA insulted mice tends to restore the levels of these markers which might be attributed to decreased hypoxia and reduction in tumor growth by an enhancement of apoptosis [18,23] . Several other researchers have also supported the restoration of blood parameters upon lycopene treatment thus showing its anti-inflammatory potential [43,44] .…”
Section: Discussionmentioning
confidence: 99%
“…The role of LycT in delaying the process of hepatocarcinogenesis has already been studied in terms of diminished histopathological alterations, reduced mortality and induction of apoptosis [3,18] . Moreover, the anti-angiogenic and anti-metastatic potential of lycopene was also investigated recently in our laboratory [23] . Periodical assessment of serological markers at early stages could serve as an important parameter to evaluate the onset of hepatic pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation